Hybrid Construction

JP7668864B2Active Publication Date: 2025-04-25SOITEC SA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023213109
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2016-10-17
Filing Date
2023-12-18
Publication Date
2025-04-25
Estimated Expiration
2036-10-17

AI Technical Summary

Technical Problem

Existing hybrid structures comprising layers of piezoelectric materials, such as LiTaO3/Si heterostructures, face issues with thermal expansion mismatch leading to structural damage like buckling and poor mechanical strength during high-temperature processing, which compromises the integrity and functionality of acoustic wave devices.

Method used

A method is developed to determine a compatible thickness range for the piezoelectric layer by using sensitivity models to predict and avoid buckling, involving thinning and heat treatment steps to strengthen the bonding interface and repair defects, ensuring the layer thickness is within specific limits to withstand thermal stress without damage.

Benefits of technology

The method ensures the hybrid structure maintains mechanical integrity and functionality by preventing buckling and enhancing bonding strength, allowing for the production of high-quality acoustic wave devices without structural degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000014_0000
    Figure 00000014_0000
  • Figure 00000015_0000
    Figure 00000015_0000
  • Figure 00000015_0001
    Figure 00000015_0001
Patent Text Reader

Abstract

To provide a method for manufacturing a hybrid structure comprising an effective layer of a material that has an effective thickness, is arranged onto a support substrate having a support thickness and a thermal expansion coefficient lower than that of the effective layer, and has a value of the thermal expansion coefficient that is different from the thermal expansion coefficient of the support substrate.SOLUTION: In the above method, a threshold value thickness that is arranged onto a support substrate, is thinned, and is determined by a middle thickness of a layer, is determined by a first sensitivity model. Their input parameter contains: a support thickness; a thermal expansion coefficient of a donor substrate and a thermal expansion coefficient of a support substrate; an annealing temperature; and a maximum size of an area where is found in a bonding boundary surface with a bonding structure and is not bonded. An upper limit of a range of the middle thickness is related to a breaking mechanism, a breaking of the material construction the support substrate occurs when an elastic energy exceeds a critical value, and a lower limit of the range is related to a size of a zone where is not adhered.SELECTED DRAWING: Figure 2a
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of manufacturing hybrid structures, in particular structures comprising layers of piezoelectric material. [Background technology]

[0002] In the field of acoustic surface or volumetric wave devices (the English terms "SAW" for "Surface Acoustic Wave" and "BAW" for "Bulk Acoustic Wave"), heterostructures comprising a layer of lithium tantalate (LiTaO3) arranged on a silicon substrate are gaining increasing interest because, on the one hand, they are compatible with standard microelectronic equipment and methods, which offer growth opportunities and lower costs thanks to the silicon support substrate, and, on the other hand, they have technical advantages, such as the fact that the frequency response of SAW devices is less dependent on temperature, as explained in Non-Patent Document 1.

[0003] For example, LiTaO3 / Si heterostructures can be produced by assembly through bonding and by molecular bonding of two LiTaO3 and Si substrates, respectively. For the manufacture of acoustic wave devices on these heterostructures, it is advantageous to be able to apply temperatures above 200°C or 250°C, in order to allow the use of materials and processes that ensure good performance of the devices.

[0004] Especially at temperatures above 200 °C, preservation of the bonding interface between the LiTaO3 layer and the Si support substrate is one of the key factors in achieving good mechanical strength of the structure.

[0005] Therefore, before the manufacturing step of the acoustic wave device, it seems important to strengthen the energy of the interface of the heterostructure, and in the case of heterostructures manufactured by bonding a layer onto a support substrate by molecular adhesion, the bonding interface can be strengthened in particular by applying a heat treatment in a temperature range of about 200 to 300° C. Therefore, due to the significant difference in the thermal expansion coefficients of both materials (CTE, which is an abbreviation for "Coefficient of Thermal Expansion" according to the English terminology), there is a problem of applying such a heat treatment to the heterostructure without damaging it.

[0006] On the other hand, when a heterostructure with a very thin layer of LiTaO3 is required (e.g. for the manufacture of bulk acoustic wave devices), one solution is to transfer the layer using the Smart Cut® method, which involves a buried weak surface in a LiTaO3 donor substrate by introducing light species such as hydrogen or helium, a direct bonding (by molecular attachment) of this donor substrate onto a silicon support substrate, and a separation at the level of the buried weak surface to transfer a surface layer of LiTaO3 onto Si. It is known that the surface layer after transfer still has defects and light species within its thickness. Therefore, it is advantageous to repair this layer by performing an annealing in a suitable temperature range to allow the repair of defects and the expulsion of light species without compromising the quality of the transferred thin layer or the mechanical strength of the heterostructure. For example, for a layer of LiTaO3, a suitable temperature range is between 400° and 600°C.

[0007] The problem, again, is that LiTaO3 / Si heterostructures can barely support these high thermal budgets, given the very large difference in thermal expansion coefficients between the two materials.

[0008] During the manufacture of hybrid or heterostructures, when the surface layer disposed on the support substrate is as thin as possible, it is customary to carry out a heat treatment having a high temperature in order to limit the stresses and deformations (as may be manifested as substrate curvature) in the hybrid structure. For example, when the thickness of the silicon surface layer is less than about 100 nm and the thickness of the large silica substrate is about 700 microns, one can refer to a hybrid structure of the silicon-on-solid silica type or silicon-on-sapphire type, which can withstand annealing as high as 850°C without suffering prohibitive damage. For thicker surface layer thicknesses, typically 1 micron, the maximum applicable temperature without causing damage drops, for example, to about 600°C. For thicker top layer thicknesses, for example 700 microns, the maximum applicable temperature without causing damage drops, for example, to around 100-150°C.

[0009] For a hybrid structure consisting of a layer of LiTaO3 (e.g. 10 microns thick) placed on a silicon substrate (e.g. 150 mm diameter, 625 microns thick), the applicant used this state of the art knowledge, which applied the annealing temperature required to strengthen the bonding interface (i.e. 250°C) to the final hybrid structure with the finest possible surface layer (10 microns of LiTaO3 on 625 microns of Si). The applicant then observed an unexpected result, namely a significant degradation of the layer due to the so-called "buckling" phenomenon, corresponding to a local buckling deformation of the LiTaO3 layer, which made the hybrid structure unusable. [Prior art documents] [Non-patent literature]

[0010] [Non-Patent Document 1] K. Hashimoto, M. Radota and al., “Recent development of temperature compensated SAW devices”, IEEE Ultrasound. Symp. 2011, pages 79 to 86, 2011. Symp. 2011, pages 79 to 86, 2011 Summary of the Invention [Problem to be solved by the invention]

[0011] One of the objects of the present invention is therefore to propose a method for producing a hybrid structure and to find a solution to the disadvantages of the prior art. In particular, the object of the present invention is to propose a method for applying the required heat treatment without damaging the hybrid structure. [Means for solving the problem]

[0012] The present invention relates to a method for manufacturing a hybrid structure comprising an effective layer of piezoelectric material having an effective thickness disposed on a support substrate having a support thickness and a thermal expansion coefficient smaller than the thermal expansion coefficient of the effective layer, the method comprising the steps of: a) providing a bonded structure comprising a donor substrate of piezoelectric material and a support substrate, the bonded structure having a bonded interface between the two substrates; b) a first step of thinning the donor substrate to form a thinner layer having an intermediate thickness disposed on a support substrate, the assembly forming a thinned structure; c) a heat treatment step of the thinned structure at an annealing temperature; d) after step c), a second thinning step of the thinned layer to form a useful layer; It should consist of The method is notable in that it comprises, prior to step b), a step a') of determining a range of intermediate thicknesses that avoids degradation of the thinned structure (6') during step c), the range being defined by a threshold thickness and a maximum thickness, and the intermediate thickness of the thinned layer being selected within this range.

[0013] The manufacturing method according to the invention therefore makes it possible to apply to the thinned structure, for which a compatible thickness range of the thinned layer has been previously determined, a heat treatment at the required annealing temperature in order to consolidate the bonding interface or to repair all or part of the defects present in the thinned layer (which will become the effective layer), said heat treatment is generally not applicable to the final hybrid structure with the effective layer of effective thickness without causing damage to the effective layer, especially when non-bonded areas (bonding defects or pre-existing engraved patterns on the assembled faces of the substrates) are found at the bonding interface.

[0014] According to advantageous characteristics of the invention, the following are provided, either alone or in combination:

[0015] The threshold thickness is determined from a first sensitivity model, whose input parameters include the support thickness, the thermal expansion coefficients of the donor substrate and the support substrate, the annealing temperature, and the maximum size of the unbonded area that can be found at the bonding interface of the bonded structure.

[0016] ● The maximum thickness is determined from a second sensitivity model, whose input parameters include the support thickness (of the support substrate 1), the thermal expansion coefficients of the donor substrate 2 and the support substrate 1, and the required annealing temperature in the thermal treatment of step c).

[0017] ● The manufacturing process includes a step a”) of reusing the bonded structure after step a′) and before step b) when the determining step a′) establishes an upper threshold thickness that is at the maximum thickness or a maximum thickness that is lower than the effective thickness.

[0018] The recycling step a″ involves separation of the bonded structures at the bond interface.

[0019] The reuse step a”) comprises the reuse of the donor substrate and the support substrate resulting from the separation for a new step a) providing a bonded structure.

[0020] The second thinning step d) may further comprise the step of thinning the support substrate.

[0021] ●The active layer is composed of a material selected from lithium tantalate (LiTaO3), lithium niobate (LiNbO3), aluminum nitride (AlN), and zinc oxide (ZnO).

[0022] The support substrate is made of a material selected from the group consisting of silicon, III-V semiconductors, silicon carbide, glass, and sapphire.

[0023] The support substrate comprises one or more surface layers.

[0024] The invention further relates to a hybrid structure comprising an active layer of piezoelectric material having an effective thickness of less than 50 microns assembled to a support substrate having a thermal expansion coefficient smaller than that of the active layer, the hybrid structure being characterized in that the bond interface between the active layer and the support substrate has a thermal expansion coefficient of less than 1000 mJ / m 2 and at least one unbonded zone between 1 and 1000 microns in size. [Brief description of the drawings]

[0025] Other features and advantages of the present invention will become apparent from the following detailed description of the invention which proceeds with reference to the accompanying drawings. [Figure 1a] 1 illustrates a method for manufacturing a hybrid structure according to the present invention. [Figure 1b]1 illustrates a method for manufacturing a hybrid structure according to the present invention. [Figure 1c] 1 illustrates a method for manufacturing a hybrid structure according to the present invention. [Figure 2a] 11A-11C show three different configurations of thickness ranges for effective thickness resulting from the determining step according to the present invention. [Figure 2b] 11A-11C show three different configurations of thickness ranges for effective thickness resulting from the determining step according to the present invention. [Figure 2c] 11A-11C show three different configurations of thickness ranges for effective thickness resulting from the determining step according to the present invention. [Diagram 3] 3A-3D illustrate different stages of a manufacturing process according to the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The invention relates to a method for manufacturing a hybrid structure 60 (FIG. 1c) comprising an active layer 20 of piezoelectric material arranged on a support substrate 1 having a supporting thickness and a thermal expansion coefficient smaller than the thermal expansion coefficient of the active layer 20.

[0027] The method comprises a step a) of providing a bonded structure 6 comprising a donor substrate 2 of piezoelectric material and a support substrate 1. The bonded structure 6 has a bonded interface 5 between these two substrates 1, 2 (Fig. 1a). For example, the donor substrate 2 can be made of a material selected from the group consisting of lithium tantalate (LiTaO3), lithium niobate (LiNbO3), aluminum nitride (AlN), zinc oxide (ZnO). The support substrate can be made of a material selected from the group consisting of silicon, III-V semiconductors, silicon carbide, glass, sapphire. One and / or the other of the substrates 1, 2 can optionally contain, on their faces to be assembled, components (all or part of a microelectronic circuit) or etched patterns, the components can be formed from stacked layers of different nature with a pattern, the etched patterns can be formed by cavities intended to ensure functionality in the final device produced on the hybrid structure 60. The assembly of the bonded structure 6 is advantageously carried out by molecular bonding between the donor substrate 2 and the support substrate 1. Optionally, an intermediate layer, such as a layer of silicon oxide, silicon nitride or other layer, which strengthens the adhesion molecule bond, can be added to one or both substrates prior to assembly. Advantageously, the substrates 1, 2 are also subjected to cleaning and / or front side activation prior to assembly in order to strengthen the quality and energy of the bond interface 5 formed after assembly.

[0028] The term "unbonded zone" hereafter refers to a localized zone at the bond interface where the surfaces of the two substrates are not in intimate contact, except for the unbonded peripheral crown at the edge of the assembled substrates, which forms an exclusion zone. The "unbonded area" is generally surrounded by the bonded area. The unbonded zone may be associated with a bond defect, for example due to the presence of particles or other contamination (such as hydrocarbons) at the bonded interface 5 of the bonded structure 6. It may also be associated with the presence of etched patterns or localized topography on the donor substrate 2 or the support substrate 1 due to the presence of components or cavities on the respective faces to be assembled, or laser marks (for example to ensure substrate traceability).

[0029] After the assembly step, the method includes a step b) corresponding to a first step of thinning the donor substrate 2 to form a thin layer 2' with intermediate thickness, arranged on the support substrate 1, thus forming, overall, a thinned structure 6' (Fig. 1b). The donor substrate 2 is thinned at its rear face 4 by mechanical, mechanochemical and / or chemical etching techniques or by a Smart Cut® type process well known to those skilled in the art. For example, the donor substrate 2 can be thinned by "grinding" (mechanical thinning) and then by chemical-mechanical polishing. This thinning step precedes a heat treatment step c), whose function can be to consolidate the bonding interface 5 or to repair defects in the thinned layer 2' that becomes the effective layer 20. It is therefore important that the thinning step b leads to obtaining a thinned structure 6' that is compatible with the heat treatment required in the subsequent step c).

[0030] The manufacturing method is therefore notable in that it comprises, before the thinning step b), a step a') of determining an intermediate thickness range for the thinned layer 2', intended to avoid degradation of the thinned structure during the heat treatment of step c). The range is defined by a threshold thickness and a maximum thickness, and therefore the intermediate thickness of the thinned layer 2' is selected within this range.

[0031] The threshold thickness is determined from a first sensitivity model, whose input parameters include the support thickness (of the support substrate 1), the thermal expansion coefficients of the donor substrate 2 and the support substrate 1, the annealing temperature required in the thermal treatment of step c), and the maximum size of the unbonded area that can be found at the bonding interface 5 of the bonded structure 6.

[0032] The first sensitivity model is established from an equation reflecting the stress relaxation of a thin layer upon pressure on a substrate. The phenomenon of stress relaxation of a thin layer, such as "buckling", requires the presence of a non-bonded zone at the interface between the thin layer and the substrate. The buckling threshold stress required to initiate stress relaxation of a thin layer, which corresponds to a local buckling deformation of the layer, is given by:

[0033]

number

[0034] can be expressed as E2 is the Young's modulus of the thin layer, V2 is the Poisson's ratio of the thin layer, h2 is the thickness of the thin layer, and r is the radius of the unbonded zone between the thin layer and the substrate. Stress can be expressed as the force applied per unit area on the cross section (length x thickness) of the thin layer. To ignore the length of the cross section and only consider the thickness h2 of the thin layer, the critical force normalized by the length in N / m is

[0035]

number

[0036] It is possible to express

[0037]

number

[0038] Considering that the thin layer corresponds to the thinned layer 2', E2, V2 are therefore respectively the Young's modulus and the Poisson's ratio of the piezoelectric material constituting the thinned layer 2', h2 is the intermediate thickness and r is the maximum radius of the non-bonded area present at the bonding interface 5 of the bonded structures 6. The size of the non-bonded area found at the bonding interface 5 can be determined, for example, by imaging in white light or infrared light according to the material that is part of the bonded structures 6, or by acoustic microscopy, a technique that is particularly advantageous for detecting non-glued areas of small size. Thus, the maximum radius of the non-bonded area at the bonding interface 5 (which may be related to bonding defects or pre-existing patterns on one or the other of the assembled faces of the donor substrate 2 and the support substrate 1) can be obtained for each bonded structure 6.

[0039] Equation {Equation 2} indicates that the "buckling" phenomenon is more likely to occur if the intermediate thickness h2 of the thinned layer 2' is insufficient (i.e., it is more likely to occur if the normalized force

[0040]

number

[0041] ) and that the maximum radius r of the unbonded area is large.

[0042] The support thickness h1 of the support substrate 1 and its mechanical properties (E1, its Young's modulus) are also known, as is the required annealing temperature applied to the thinned structure 6' during the heat treatment of step c). Thus, the normalized pressure force F applied to the thinned layer 2' during the heat treatment of step c) is known. norm It is possible to express

[0043]

number

[0044] ρ is the radius of curvature of the thinned structure 6′;

[0045]

number

[0046] ΔCTE is the difference between the thermal expansion coefficients of the respective materials of the thinned layer 2′ and the support substrate 1, ΔT is the differential temperature between room temperature and the applied annealing temperature, and the term K(h1,h2) is

[0047]

number

[0048] It is expressed as follows.

[0049] Therefore, the threshold thickness of the range is given by Equation 5.

[0050]

number

[0051] It can be determined by solving:

[0052]

number

[0053] The threshold thickness is h 2seuil It is.

[0054] The threshold thickness corresponds to an intermediate thickness below which the "buckling" phenomenon has a high probability of occurrence and takes into account the characteristics of the thinned structure 6' (the type of material it is made of, the maximum size of the non-bonded zones that can be found at the bonding interface 5, the thickness of the support substrate) and the annealing temperature applied during the heat treatment of step c). It should be noted that the "buckling" phenomenon may involve an expansion of the non-bonded zones, preferably perpendicular to the crystal axis with the highest expansion coefficient. This expansion may be all the more pronounced the lower the energy of the bonding interface 5. It is therefore of great importance in the construction to avoid the appearance of "buckling".

[0055] The first sensitivity model therefore links the threshold thickness to a set of characteristic parameters of the thinned structure 6' and to the thermal stresses it must experience.

[0056] The maximum thickness is determined from a second sensitivity model, whose input parameters include the support thickness (of support substrate 1), the thermal expansion coefficients of donor substrate 2 and support substrate 1, and the required annealing temperature in the thermal treatment of step c).

[0057] The second sensitivity model is established from an equation reflecting the fracture of the material constituting the support substrate 1, constrained in its expansion in the thinned structure 6' during the heat treatment. The elastic energy E stored in the support substrate 1, in the case of a thinned structure 6' comprising a thinned layer 2' of different nature and a support substrate 1, to which a heat treatment is applied, is expressed as follows:

[0058]

number

[0059] The material constituting the support substrate 1 breaks when the elastic energy E is:

[0060]

number

[0061] This occurs when a critical value given by

[0062] K 1c is the tensile strength of the material that constitutes the support substrate 1.

[0063] Therefore, the maximum thickness of the range is given by the formula E = E rupture It can be determined by solving:

[0064]

number

[0065] The maximum thickness is h 2plafond It is.

[0066] The maximum thickness corresponds to the intermediate thickness of the thinned layer 2', above which there is a high probability of a fracture of the support substrate 1, and takes into account the characteristics of the thinned structure 6' (the type of material of which it is made, the thickness of the support substrate 1) and the annealing temperature applied during the heat treatment of step c).

[0067] The second sensitivity model therefore links the maximum thickness to a set of characteristic parameters of the thinned structure 6' and to the thermal stresses it must experience.

[0068] A heterostructure such as the thinned structure 6', when subjected to a thermal treatment, experiences stresses and deformations due to the differential expansion of the two materials that compose it. The structure 6' deforms by acquiring a curvature that can result in different failure modes: fracture of the support substrate 1, buckling of the thinned layer 2', formation of dislocations or slip planes in the structure (especially in the thinned layer 2'), lift-off at the edges of the thinned structure 6', etc. Experimentally, the applicant has realised that in the case of a thinned structure 6' comprising a layer of piezoelectric material and a support substrate made of a material with a lower thermal expansion coefficient, the two dominant failure modes were, on the one hand, the breakage of the support substrate 1 (phenomenon of fracture of the material beyond a critical fracture energy) and, secondly, local buckling at the level of the unbonded areas of the thinned layer 2' (phenomenon of stress relaxation of a thin layer upon application of pressure, called "buckling"). Therefore, the two sensitivity models established by the applicant from Equations {Equation 6} and {Equation 9} are well suited to determine the thickness range for the thinned layer 2' in the case of a heterogeneous thinned structure 6', in which the thinned layer 2' is made of a piezoelectric material.

[0069] Thus, following step a'), a thickness range is obtained, defined by the determined threshold thickness and a maximum thickness, as illustrated in figures 2a to 2c.

[0070] According to a first variant of implementing the manufacturing method, the effective thickness of the expected useful layer 20 for the final hybrid structure 60 is smaller than the defined thickness range (FIG. 2a), which is the case for a thickness range that is compatible with the envisaged final structure. The manufacturing method according to the invention comprises, after a step a') for determining the thickness range for which it is compatible, as mentioned above, a step b) of thinning of the donor substrate 2 to form a thinned layer 2'. The intermediate thickness of the thinned layer 2' is then selected to be within the range, i.e. between a threshold thickness and a maximum thickness. The process then comprises a step c) of heat treatment at the annealing temperature required for the thinned structure 6'. For example, the annealing temperature can vary between 200° C. and 600° C., depending on the type of hybrid structure expected and according to the purpose of the heat treatment, such as consolidating the bond interface 5, repairing defects or diffusing light chemical species within the thickness of the thinned layer 2' (intended to become the useful layer 20). The heat treatment can include entry and exit at a low temperature, e.g., 100°C, with an increase and decrease in temperature ramp, e.g., between 0.5 and 5° / min, and a hold at the required annealing temperature, e.g., between 200°C and 600°C, for a period ranging from 30 minutes to several hours.

[0071] After step c) of the thermal treatment, the method comprises a step d) corresponding to a second step of thinning the thinned layer 2' to form an effective layer 20 with an effective thickness, arranged on the support substrate 1, all forming the final hybrid structure 20 (FIG. 1c). The layer 2' is then thinned again at its face 4 by the techniques of mechanical thinning, mechanochemical and / or chemical etching and / or thinning by the Smart Cut® method. For example, the layer 2' can be thinned by a mechanochemical polishing sequence followed by cleaning. The hybrid structure 20 thus formed can then be used for the production of electronic devices, the properties of which (bonding energy of the bonding interface 5 and / or quality of the effective layer 20) have been improved by the realization of the method according to the invention. Usually, the development step of the device does not require a thermal treatment applied at a temperature as high as the annealing temperature of step c) of the method.

[0072] According to a second embodiment variant of the manufacturing method, the effective thickness of the expected effective layer 20 for the final hybrid structure 60 is within a defined thickness range (FIG. 2b), which is the case for a thickness range that is compatible with the envisaged final structure. The manufacturing method according to the invention comprises, as mentioned above, after step a'), a step b) of thinning the donor substrate 2 to form a thinned layer 2'. The intermediate thickness of the thinned layer 2' is advantageously chosen to be within a range, in particular it is chosen to be equal to or substantially greater than the effective thickness. The process then comprises a step c) of heat treatment at the annealing temperature required for the thinned structure 6'. For example, the annealing temperature can vary between 200 ° C and 600 ° C depending on the type of hybrid structure 60 expected and according to the purpose of the heat treatment.

[0073] After the heat treatment in step c), the method includes a step d) corresponding to a second step of thinning the thinned layer 2' to form an effective layer 20 with an effective thickness, arranged on the support substrate 1, all forming the final hybrid structure 60. According to this second embodiment variant, the step b) of thinning the layer to be thinned already brings the intermediate thickness substantially to the effective thickness. Step d) can therefore essentially consist of a polishing step with slight removal (according to the English terminology "touch polish") and a cleaning sequence to improve the surface condition of the face 4 of the effective layer 20. The hybrid structure 20 thus formed can then be used for the development of electronic devices, in particular acoustic wave devices.

[0074] According to a third variant of implementing the manufacturing method according to the invention, the effective thickness of the effective layer 20 envisaged for the final hybrid structure 60 is greater than the defined thickness range (FIG. 2c), in other words the effective thickness is greater than the maximum thickness. This configuration reflects the fact that the defined thickness range (determined by the sensitivity model and from the properties of the bonded structure 6 and the required annealing temperature) is not compatible with the envisaged final hybrid structure 20.

[0075] This thickness range configuration (FIG. 2c), which is not compatible with the expected hybrid structure, can be the result of an unsuitable support substrate. The manufacturing method according to the invention then comprises a step a”) of reusing the bonded structure 6. Step a”) consists of achieving a lift-off of the bonded structure 6 at the bonded interface 5, leading to a separation of the donor substrate 2 and the support substrate 1. The separation can be performed by inserting a bevel-shaped tool between the chamfered edges of the two substrates, the donor substrate 2 and the support substrate 1 of the bonded structure 6. After separation, the reusing step a”) further comprises the reuse of the detached donor substrate 2 and the support substrate for a new step a) of providing the bonded structure 6. To use a support substrate 1 of a larger thickness and to provide a new bonded structure 6, the reusing step a”) can be utilized. An increase in the support thickness in particular increases the value of the maximum thickness, the aim of which is to find a compatible thickness range, i.e. a range with a maximum thickness greater than the expected effective thickness. The second thinning step d) according to the method in this case also comprises a thinning step of the rear side of the support substrate 1 in order to return it to the required support thickness for the final hybrid structure 60. This additional thinning step can consist of a mechanical, mechanochemical or chemical thinning.

[0076] Configurations in which the thickness range is not compatible with the expected hybrid structure (FIG. 2c) may also be related to the fact that the annealing temperature is too high. One can then choose to lower the annealing temperature applied in the thermal treatment step c). The reuse step a”) can be used to apply a different surface pretreatment (potentially more complex or expensive, but necessary in this case) to the substrates 1 and 2 before their assembly, making it possible, for example, to enhance the bonding energy after the thermal treatment at a lower temperature. A new thickness range is then determined before continuing the process.

[0077] According to a fourth embodiment variant of the manufacturing method, the threshold thickness determined in step a') is greater than the maximum thickness determined in the same step (configuration not shown). In this case, the thickness range is still considered to be incompatible with the expected structure, since it does not exist (thickness range is defined by a threshold thickness lower than the maximum thickness). In this case, the maximum size of the non-bonded area found at the bonding interface 5 may be too large to allow a compatible thickness range. The manufacturing method according to the invention then comprises a step a") of reusing the bonded structure 6. Step a") consists of achieving a lift-off of the bonded structure 6 at the bonding interface 5, leading to a separation of the donor substrate 2 and the support substrate 1. The detachment can be performed by applying a stress at the interface between the two substrates of the bonded structure 6, the donor substrate 2 and the support substrate 1. After separation, the recycling step a”) comprises the reuse of the detached donor substrate 2 and the support substrate 1 for a new step a) providing a bonded structure 6. Assuming that the non-bonded zone of maximum size was involved in the bonding failure, the recycling step a”) makes it possible to eliminate this defect by a new cleaning and pretreatment of the surfaces of the substrates 1, 2 to be assembled.

[0078] If it is difficult to reduce the size of the unbonded area found at the bonding interface 5 (for example in the case where there is a pre-existing pattern or cavity on one of the two substrates to be assembled, carrying a specific function), the reuse step a”) can for example be used to use and modify the assembly conditions, in order to allow a subsequent reduction of the temperature that has to be applied in step c) and to provide a new bonded structure 6.

[0079] The main steps of the method according to the invention are illustrated in (Figure 3).

[0080] The manufacturing method according to the invention makes it possible to apply a heat treatment at an annealing temperature, required to consolidate the bonding interface 5 or to repair defects in the thinned layer 2' (which will become the effective layer 20), to the thinned structure 6' for which a compatible thickness range for the thinned layer 2' has been previously determined. Heat treatment is generally not applicable to the final hybrid structure 60 having (i.e.) the effective thickness of the effective layer 20 without causing damage to the effective layer 20, especially when non-bonded areas (pre-existing bonding defects or engraved patterns on the assembled surfaces of the substrates 1, 2) are found at the bonding interface 5.

[0081] Moreover, the step a') for determining a compatible thickness range makes it possible to identify when it is necessary to reuse the bonded structure 6, before engaging in the thinning step b), which therefore makes it possible to increase the manufacturing yield.

[0082] The invention also relates to a hybrid structure 60 (FIG. 1c) comprising an effective layer 20 of piezoelectric material with an effective thickness of less than 50 microns assembled to a support substrate 1 having a thermal expansion coefficient smaller than that of the effective layer 20. The bond interface 5 between the effective layer 20 and the support substrate 1 has a thermal expansion coefficient of less than 1000 mJ / m 2or more and at least one unbonded area between 1 and 1000 microns in size. The active layer 20 is made of a material selected from the group consisting of lithium tantalate (LiTaO3), lithium niobate (LiNbO3), aluminum nitride (AlN), zinc oxide (ZnO). For example, its thickness is between 0.1 microns and 50 microns. The support substrate is made of a material selected from the group consisting of silicon, III-V semiconductors, silicon carbide, glass, sapphire. For example, its thickness is between 0.1 microns and 50 microns. The support substrate can also comprise one or more different types of surface layers. For example, the support substrate can consist of a monocrystalline silicon substrate, in particular polycrystalline silicon, having a surface layer capable of trapping charges at the edge of the surface to be assembled, it can also consist of a SOI substrate (silicon on insulator), the surface layer of which is in silicon oxide and silicon, or in a SOI substrate provided with a charge trapping layer under the oxide layer.

[0083] Example 1: The support substrate 1, made of silicon (Si) with a diameter of 150 mm and a thickness of 725 microns, has etched patterns evenly spaced over the entire surface to be assembled. These can have the function of alignment marks, for example, or constitute cavities for the manufacture of suspended membranes or even for the creation of electrical contacts in the final hybrid structure 60 on which the device will be developed. The support substrate 1 also comprises an oxide layer on the surface to be assembled. It is bonded by molecular bonding together with a donor substrate 2 made of lithium tantalate (LiTaO3) of the same diameter to provide a bonded structure 6. A microscope acoustic control step makes it possible to detect and measure the non-bonded areas at the bonded interface 5, generated by the patterns. The maximum size of the non-bonded areas corresponds to a radius r of 500 microns.

[0084] The expected final hybrid structure 60 has a useful layer of 10 microns and a supporting substrate of 725 microns. The annealing temperature applied is 250° C. to make the bond interface 5 strong enough so that the hybrid structure 60 will support the subsequent steps of developing an acoustic wave device.

[0085] Step a') determines the threshold thickness and the maximum thickness by h 2threshold = 28 μm, and h 2ceiling = 32 μm. The thickness range obtained is compatible with the anticipated hybrid structure 60, and the effective thickness is less than the range.

[0086] The thinning in step b), consisting of mechanical thinning followed by chemical-mechanical polishing and chemical cleaning, allows the formation of a thinned layer 2' with an intermediate thickness of 30 microns. Then, the heat treatment in step c) is carried out. The furnace entry is at 100° C. and the ramp temperature increase is 1° / min until it reaches a peak at 230° C. over a period of 4 hours. Then, a ramp temperature decrease of 1° / min is caused up to 100° C., after which the thinned structure 6' is removed from the furnace. The thinned structure 6' then undergoes a second step of thinning the thinned layer 2' to a thickness of 10 microns in order to form the useful layer 20.

[0087] The resulting hybrid structure 60 is thus integrated and has a bonding energy of 1000 mJ / m 2 and beneficial integrated layers having sizes ranging between 100 and 500 microns, without degradation linked to the "buckling" phenomenon, despite the presence of unbonded areas at the interface. Such hybrid structures 60 can then be used for the development of acoustic wave devices.

[0088] Example 2: A support substrate 1, made of silicon (Si) with a diameter of 150 mm and a thickness of 725 microns and provided with an oxide layer on the face to be assembled, is joined by adhesion to a donor substrate 2 made of lithium tantalate (LiTaO3) of the same diameter to provide a bonded structure 6. A microscope acoustic control step makes it possible to detect two bond defects (unglued areas) at the bond interface 5, the maximum size of which corresponds to a radius r of 700 microns.

[0089] The expected final hybrid structure 60 has a useful layer of 10 microns and a supporting substrate of 725 microns. The annealing temperature applied is 250° C. with the aim of making the bond interface 5 strong enough so that the hybrid structure 60 will support the subsequent steps of developing an acoustic wave device.

[0090] Step a') determines the threshold thickness and the maximum thickness by h 2threshold = 28 μm, and h 2ceiling = 25 μm. The thickness range obtained is not compatible with the expected hybrid structure 60, the threshold thickness being greater than the maximum thickness.

[0091] Then, a reuse step a”) is performed in order to reduce the maximum size of the adhesive defects present at the adhesive interface 5, and the insertion of a bevel-shaped tool at the level of the adhesive interface 5 of the bonded structure 6 makes it possible to separate the donor substrate 2 and the support substrate 1. A new cleaning and surface activation sequence of the two substrates is performed before a new assembly to give a new bonded structure 6. A new acoustic microscope control step makes it possible to detect 10 defects at the adhesive interface 5, the maximum size of which corresponds to a radius r of 150 microns.

[0092] Based on the new properties of the bonded structure 6, step a') determines the threshold thickness and the maximum thickness as follows: h 2threshold = 20 μm, and h 2ceiling= 25 μm. The thickness range obtained is in turn compatible with the anticipated hybrid structure 60, with the threshold thickness being less than the maximum thickness and the effective thickness being less than the range.

[0093] The thinning step b), consisting of a mechanical thinning followed by chemical-mechanical polishing and chemical cleaning, allows a thinned layer 2' to be formed with an intermediate thickness of 23 microns. Then the heat treatment of step c) is carried out. The furnace entry is carried out at 70° C., with a ramped temperature increase gradient of 1° / min until it reaches a plateau at 250° C. over a period of 4 hours. Then a temperature ramp down of 1° / min is caused up to 100° C., after which the structure is removed from the furnace. The thinned structure 6' then undergoes a second step of thinning the thinned layer 2' to a thickness of 10 microns in order to form the useful layer 20.

[0094] The resulting hybrid structure 60 is thus integrated and has a bonding energy of 1000 mJ / m 2 or more, or 1500 mJ / m 2 10 ...

[0095] Of course, the invention is not limited to the described embodiments and examples, and variants can be provided without departing from the scope of the invention as defined by the claims.

Claims

1. 1. A method for manufacturing a hybrid structure (60) having an effective layer (20) of material with an effective thickness and with a thermal expansion coefficient value different from that of the thermal expansion coefficient of the support substrate (1), the effective layer (20) having an effective thickness and a thermal expansion coefficient smaller than that of the support substrate, the method comprising the steps of: a) providing a bonded structure (6) comprising a donor substrate (2) of said material and said support substrate (1), said bonded structure (6) having a bonded interface (5) between said support substrate (1) and said donor substrate (2); b) a first step of thinning the support substrate (1) or the donor substrate (2) to form a thinned layer (2') of intermediate thickness arranged on the support substrate (1), which overall forms a thinned structure (6'); c) a heat treatment step of said thinned structure (6') at an annealing temperature; d) a second thinning step of said thinned layer (2') after said heat treatment step c) to form said effective layer (20), The method comprises, before the first step b), a step a') of determining an intermediate thickness range that avoids a degradation of the thinned structure (6') during the thermal treatment step c) after the thermal treatment step, said range being defined by a threshold thickness and a maximum thickness, said intermediate thickness of the thinned layer (2') being selected within said range, the threshold thickness is determined from a first sensitivity model, input parameters of which include the support thickness, the thermal expansion coefficients of the donor substrate (2) and the support substrate (1), the annealing temperature, and the maximum size of an unbonded area that can be found at the bonded interface (5) of the bonded structure (6); The upper limit of the range relates to the fracture mechanism, whereby the fracture of the material constituting the support substrate (1) occurs when the elastic energy exceeds a critical value, and The lower limit of the range relates to the size of the unbonded zone. A method for manufacturing said hybrid structure (60).

2. Further thinning the thinned layer (2'), The intermediate thickness is below the range. A method for manufacturing the hybrid structure (60) of claim 1.

3. 3. The method for manufacturing a hybrid structure (60) according to claim 1 or 2, wherein the maximum thickness is determined from a second sensitivity model, the input parameters of which include the support thickness, the thermal expansion coefficients of the donor substrate (2) and the support substrate (1), and the annealing temperature.

4. 4. The method for manufacturing a hybrid structure (60) according to any one of claims 1 to 3, comprising a step a") of reusing the bonded structure (6) after the determining step a') and before the first step b) when the determining step a') establishes the threshold thickness higher than the maximum thickness or the maximum thickness lower than the effective thickness.

5. 5. The method of claim 4, wherein said recycling step a'') comprises separation of said bonded structure (6) at said bond interface (5).

6. 6. The method for manufacturing a hybrid structure (60) according to claim 5, wherein said step a″) of recycling comprises reusing said donor substrate (2) and said support substrate (1) from said separation for a new step a) of providing a bonded structure (6).

7. 7. A method for manufacturing a hybrid structure (60) according to any one of claims 1 to 6, wherein the second thinning step d) can further comprise the step of thinning the support substrate (1).

8. The effective layer (20) is made of lithium tantalate (LiTaO 3 ), lithium niobate (LiNbO 3 8. A method for manufacturing a hybrid structure (60) according to any one of claims 1 to 7, comprising a material selected from the group consisting of: aluminum nitride (AlN), zinc oxide (ZnO).

9. A method for manufacturing a hybrid structure (60) according to any one of claims 1 to 8, wherein the support substrate (1) is made of a material selected from the group consisting of silicon, III-V semiconductors, silicon carbide, glass, sapphire.

10. A method for manufacturing a hybrid structure (60) according to any one of the preceding claims, wherein the support substrate (1) is provided with one or more surface layers.

11. A method for manufacturing a hybrid structure (60) according to any one of claims 1 to 10, comprising the steps of: The method of claim 1, wherein the material has a coefficient of thermal expansion greater than a coefficient of thermal expansion of the supporting substrate.